BIOAKTIVITAS INSULIN LIKE GROWTH FACTOR–I COMPLEX PLASMA SEMINALIS KAMBING TERHADAP KUALITAS SPERMATOZOA HASIL SENTRIFUGASI - Suherni Susilowati (The East Java Biological Society, 2007)
Series of exploratived laboratory experiment have been conducted to analysed the bioactifity of Insulin Like Growth Factor – I (IGF-I) Complex protein of goat seminal plasm on the membran plasm and acrosom cap of centrifugation sperm. First experiment was conducted to identificatify and isolate IGF –I Complex of goat seminal plasm by using Native - Polyacrylamide gel electroforesis. The result of analysis of Native – PAGE indicated that IGF-I Complex have molecular weight of 150 kDa. Second experiment was conducted to role of IGF-I Complex protein on the membrane plasm and acrosom cap of centrifugation sperm. Semen was collected by using artificial vagina from eight mature goat. Immediately after initial evaluation, semen was centrifugated with Bracket and Oliphant’s (BO) for 5 minutes 1800 rpm. And then divided two groups. Each group was supplemented with 3 × 106 of sperm concentration and then into group I was supplemented with BO medium and group two was supplemented with IGF-I Complex protein. The result of this experiment indicated that percentages of intact plasm membrane and intact acrosom cap were significantly (p < 0.05), between BO medium and IGF-I protein. In conclusion, IGF- I Complex protein is the optimal in improving plasm membran and acrosom cap of centrifugation sperm